2018
DOI: 10.5527/wjn.v7.i2.65
|View full text |Cite
|
Sign up to set email alerts
|

Genetic defects in ciliary genes in autosomal dominant polycystic kidney disease

Abstract: AIMTo evaluate the genetic defects of ciliary genes causing the loss of primary cilium in autosomal dominant polycystic kidney disease (ADPKD).METHODSWe analyzed 191 structural and functional genes of the primary cilium using next-generation sequencing analysis. We analyzed the kidney samples, which were obtained from 7 patients with ADPKD who underwent nephrectomy. Each sample contained polycystic kidney tissue and matched normal kidney tissue.RESULTSIn our study, we identified genetic defects in the 5 to 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…KIF19 is a member of the kinesin-8 subclass and is associated with ciliary vascular motility and vascular depolymerization [29]. Deficiency of KIF19 is associated with hydrocephalus, female infertility and autosomal dominant polycystic kidney disease [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…KIF19 is a member of the kinesin-8 subclass and is associated with ciliary vascular motility and vascular depolymerization [29]. Deficiency of KIF19 is associated with hydrocephalus, female infertility and autosomal dominant polycystic kidney disease [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of ALMS1 can lead to significantly longer and bent cilia and reduce the activity of SMAD2/3 induced by TGF‐β1 (Alvarez‐Satta et al., 2021). In addition, it has been reported that genetic defects in ciliary genes, which are essential to ciliogenesis and include kinesin family member 19 (KIF19), are found in human ADPKD tissues and that cilia are elongated in kidney tissues from ADPKD patients (Skalická et al., 2018, Shao et al., 2020). Knockdown of the ADPKD‐related Pkd1 or Pkd2 gene encoding PC1 or PC2 can cause activation of β‐catenin in the Wnt signaling pathway (Shao et al., 2020).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…An important study assessed allelic variants in 191 structural and functional genes of the primary cilium in tissue samples from 7 PKD patients. (Skalická et al 2018) This was a significantly more high-throughput experiment compared to early studies that found one or two genes associated with familial PKD. Illumina sequencing revealed pathogenic variants in 39 genes encoding various structural components of the primary cilium.…”
Section: Targeted Next-generation Sequencingmentioning
confidence: 99%